König et al. 2020. The Akie Language of Tanzania - Mietzner, Angelika (AAeO - Afrikanistik-Aegyptologie-Online, 2021)
König, Christa, Bernd Heine, Karsten Legère & Ingo Heine. 2020. The Akie Language of Tanzania. Texts and Dictionary. East African Languages and Dialects, vol.29. Cologne: Köppe. 88 photos, 1 drawing. €69,80. ISBN978-3-89645-714-1